GIS-material for the archaeological project: Planned removal of level crossing on Stångådalsbanan [rail road] by Storängsberget - Swedish National Heritage Board, UV Öst (Uppsala University, 2014)
The information in the abstract is translated from the archaeological report:
By reqest of the County Administrative Board of Östergötland and due to a planned removal of a level crossing along the Stångådalsbanan railway, the Swedish National Heritage Board's Contract Archaeology Service, UV Öst, has performed an archaeological assessment (phase 1) in Storängsberget, Vist parish, Linköpings municipality. The survey area was much disturbed by recent ploughing, and only one prehistoric feature was found. The area was thus not considered being of interest from an archaeological point of view.

Purpose:

The information in the purpose is translated from the archaeological report:
The purpose of the archaeological assessment was to determine whether any archaeological remains were to be affected by the planned development project.

The ZIP file consist of GIS files and an Access database with information about the excavations, findings and other metadata about the archaeological survey.

Informationen i sammanfattning är hämtad ur rapporten för undersökningen:
På uppdrag av Länsstyrelsen i Östergötland har Riksantikvarieämbetet UV Öst utfört en arkeologisk utredning, etapp 2 inom Storängsberget, Vists socken, Linköpings kommun. Utredningen föranleddes av en planerad borttagning av en plankorsning på Stångådalsbanan. Inom den aktuella exploateringsytan, som var starkt påverkad av senare tidens åkerbruk, påträffades endast en förhistorisk anläggning. På grund av detta bedöms området inte vara intressant ur arkeologisk synvinkel.

Syfte:

Informationen i syfte är hämtad ur rapporten för undersökningen:
Syftet med den arkeologiska utredningen, etapp 2, var att med hjälp av sökschaktsgrävning utröna om en fast fornlämning berörs av det planerade exploateringsprojektet.

ZIP-filen innehåller GIS-filer samt en Access datafil vilka innehåller information om schakt, fyndföremål, lämningstyper samt annan metadata om den arkeologiska undersökningen.
GIS-material för arkeologiskt projekt: Planerad borttagning av plankorsning på Stångådalsbanan vid Storängsberget
Keywords: HISTORY; HISTORIA; History and Archaeology; Historia och arkeologi; Archaeology; Arkeologi